(untitled) (Journal of Educational Sciences, 2016)
The article offers a periodization of the development of choreographic education in Kazakhstan. The author has identifi ed four steps of: 20-years – until 1934 years. XX century – rise of the dance groups in Kazakhstan; 1934 – to 40- years XX century – formation of the classical system of training the skill of the ballet; 50-80- years – development and creation of the national system of choreographic education of Kazakhstan; 90- years XX century – to present time – the stage of further improvement and development of the ballet school and choreographic education.